Pengaruh Attractiveness, Trustworthiness, dan Expertise Beauty Vlogger terhadap Minat Beli Produk Kecantikan di Youtube (Studi pada Mahasiswi di Tiga Universitas Yogyakarta) - Angela Selmi Gusniar (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2020)
This research aims to identify: 1) Attractiveness, Trustworthiness, and Expertise and buying interest in beauty vloggers, 2) The effect of attractiveness, trustworthiness, and beauty vlogger expertise simultaneously on buying interest in beauty products, 3) Effect of attractiveness, trustworthiness, and beauty expertise vloggers in a partial (individual) interest in buying beauty products. Data were collected using a questionnaire. The sample used in this study amounted to 100 respondents. Data analysis techniques used to test hypotheses are multiple linear regression, F test and t test. the results showed that 1) attractiveness beauty vlogger was classified as very good, trustworthiness beauty vlogger was classified as good, and beauty vlogger expertise was classified as very good, and buying interest was classified in the high category 2) Attractiveness, trustworthiness, expertise of beauty vlogger simultaneously affected the product buying interest beauty, 3) Attractiveness beauty vlogger partially has no effect on buying interest, trustworthiness and expertise of beauty vloger partially influences the buying interest of beauty products.